Traditional Chinese Medicine Compound-Loaded Materials in Bone Regeneration - Shi, Guiwen; Yang, Chaohua; Wang, Qing; Wang, Song; Wang, Gaoju; Ao, Rongguang; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2022)
Bone is a dynamic organ that has the ability to repair minor injuries via regeneration. However, large bone defects with limited regeneration are debilitating conditions in patients and cause a substantial clinical burden. Bone tissue engineering (BTE) is an alternative method that mainly involves three factors: scaffolds, biologically active factors, and cells with osteogenic potential. However, active factors such as bone morphogenetic protein-2 (BMP-2) are costly and show an unstable release. Previous studies have shown that compounds of traditional Chinese medicines (TCMs) can effectively promote regeneration of bone defects when administered locally and systemically. However, due to the low bioavailability of these compounds, many recent studies have combined TCM compounds with materials to enhance drug bioavailability and bone regeneration. Hence, the article comprehensively reviewed the local application of TCM compounds to the materials in the bone regeneration in vitro and in vivo. The compounds included icariin, naringin, quercetin, curcumin, berberine, resveratrol, ginsenosides, and salvianolic acids. These findings will contribute to the potential use of TCM compound-loaded materials in BTE.